Group-Based Cognitive Behavioral Therapy Training Improves Mental Health of SME Entrepreneurs : Experimental Evidence from Conflict-Affected Areas of Pakistan - Saraf, Priyam (World Bank, Washington, DC, 2019)
Mental health, well-being, and lasting economic outcomes are intimately connected. However, in geographies marked by fragility, conflict, and violence (FCV), entrepreneurs of small and medium size enterprises (SMEs) experience chronic stress and poor mental health on a regular basis. These issues can hamper performance and quality of life for the entrepreneurs, and can dampen the benefits of existing financial and business assistance programs. Few proven rigorous interventions are known. This study tests the hypothesis that a five-week group Cognitive Behavioral Therapy (CBT) training called Problem Management Plus for Entrepreneurs (PM+E), in combination with financial assistance, could be more effective at reducing psychological stressors of SME entrepreneurs in FCV contexts than financial assistance alone. Meaningful and statistically significant improvements in mental health were achieved, with improvements persisting and increasing beyond the immediate post-intervention period. Based on analysis of pooled data across two follow-up rounds (at five weeks and three months post-intervention), entrepreneurs in the treatment group experienced statistically significant reduction in the intensity and prevalence of depression and anxiety symptoms (measured by the Patient Health Questionnaire Anxiety and Depression Scale) and higher levels of well-being (measured by the World Health Organization Well-Being Index) compared with the control group. The effect was marked for those experiencing mild/moderate levels of depression and anxiety, suggesting the clinical value of such low touch interventions. Overall, the study demonstrates that empirical research through Randomized Control Trials (RCTs) can be conducted in challenging, FCV settings through appropriate rapid training of local researchers and non-specialist providers (NSPs) at a low cost, yielding scalable programmatic and policy level lessons.